Peningkatan Hasil Belajar Menggunakan Media Ular Tangga Pintar pada Siswa Kelas IV - Sukmawati, Laras; Mursidik, Elly’s Mursina; Hardhinata, Agung Yuli (LPPM Press, 2023)
This research is based on the mathematics learning outcomes of fourth grade students which are still below the minimum completeness criteria (KKM). Preliminary studies show that the cause of the low results in learning mathematics for students is the less optimal learning that has been designed by the teacher and the use of learning media in the class that is less interesting and varied so that during the learning process students are less active and have difficulty understanding the subject matter. From these problems, the researcher choose snakes and ladders media as an effort to improve student learning outcomes. This study aims to improve student learning outcomes through snakes and ladders media. The research method used Collaborative Classroom Action Research (PTK) which refers to plans, actions, observations, and reflections which were carried out in 2 cycles of learning for fourth grade students at SD Negeri 1 Temon. The results of the study show that the use of snakes and ladders game media can improve student learning outcomes. The increase in the success of students' scores in the pre-cycle by 23.0% increased to 46.1% in cycle I and 76.9% in cycle II, it means that there was an increase in the learning process, so it was concluded that snakes and ladders media was able to improve student learning outcomes in class IV in SD Negeri 1 Temon.